2011
DOI: 10.1158/1078-0432.ccr-10-1811
|View full text |Cite
|
Sign up to set email alerts
|

Efficient In vivo Priming by Vaccination with Recombinant NY-ESO-1 Protein and CpG in Antigen Naïve Prostate Cancer Patients

Abstract: Purpose: NY-ESO-1, one of the most immunogenic tumor antigens, is expressed in 15% to 25% of metastatic prostate cancers. The immunological and clinical effects of vaccination with recombinant NY-ESO-1 protein combined with CpG as adjuvant were evaluated.Experimental Design: In a phase I clinical study, patients with advanced prostate cancer were vaccinated with recombinant NY-ESO-1 protein (100 mg) mixed with CpG 7909 (2.5 mg) every 3 weeks intradermally for 4 doses. Objectives of the study were the safety of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 37 publications
0
55
0
1
Order By: Relevance
“…We and other groups have shown that CpG 7909 when coadministered with Melan-A-or NY-ESO-1-specific peptide-or protein-based cancer vaccines can enhance both, antigen-specific humoral and cellular immune responses against the vaccine (9)(10)(11)(12). However, as CpG-ODNs can also activate suppressive pathways of the immune system, for example, interleukin-10 production and induction of Treg cells (15,16), chemical modifications of CpG-ODNs are currently being investigated to identify the most effective CpG-ODN for the modulation of different properties of the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We and other groups have shown that CpG 7909 when coadministered with Melan-A-or NY-ESO-1-specific peptide-or protein-based cancer vaccines can enhance both, antigen-specific humoral and cellular immune responses against the vaccine (9)(10)(11)(12). However, as CpG-ODNs can also activate suppressive pathways of the immune system, for example, interleukin-10 production and induction of Treg cells (15,16), chemical modifications of CpG-ODNs are currently being investigated to identify the most effective CpG-ODN for the modulation of different properties of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…CpG-specific antibodies were measured in the serum by standard ELISA assays as previously described (12). Briefly, sera were added to 96-well plates (Nunc Maxisorb) coated with 5 mg/mL (50 mL/well) of oligodeoxynucleotides overnight at 4 C and blocked with 2% bovine serum albumin/PBS.…”
Section: Measurement Of Antibody Responses By Elisamentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal measurement of serum antibodies was performed by standard ELISA as described previously (10). Ex vivo or in vitro analysis of T cells was performed by IFN-g enzymelinked immunospot (ELISPOT) assay and by fluorescenceactivated cell sorting (FACS) analysis using peptide-MHC class I tetramer complexes as described previously (11).…”
Section: Monitoring Of Immune Responsesmentioning
confidence: 99%